2019
DOI: 10.1021/acs.iecr.9b01682
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Compounds on Reactive Adsorption Desulfurization over NiO/ZnO-Al2O3-SiO2 Adsorbents

Abstract: The effect of nitrogen compounds in FCC gasoline on reactive adsorption desulfurization (RADS)­was investigated over NiO/ZnO-Al2O3–SiO2 adsorbents. On the basis of ammonia temperature-programmed desorption (TPD), pyridine infrared radiation (Py-IR), and X-ray diffraction (XRD), adsorbents calcinated at 500 °C exhibit weak acidity and strong acidity, high Brδnsted acidity, and good dispersion of the active components. High Brδnsted acidity adsorbent presents the best RADS ability, contributing to adsorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…For Ag 2 O/SiO 2 –TiO 2 -50, the peak at 1445 cm –1 shifted to a higher wavenumber (1448 cm –1 ), which was attributed to Lewis acid center-bonded pyridine, and another peak at 1489 cm –1 appeared, which was assigned to either the Lewis acid center or the Brönsted acid center. However, no peak at around 1540 cm –1 was observed. , The case indicated that the incorporation of Ti into Ag 2 O/SiO 2 -50 led to the appearance of Lewis acid sites. As displayed in Figure b, the NH 3 -TPD profile of Ag 2 O/SiO 2 -50 showed no evident peak, indicative of the negligible acidity and the weak interaction of NH 3 with Ag + , which was desorbed by purging at a temperature of 393 K. Ag 2 O/SiO 2 –TiO 2 -50 showed a broad NH 3 desorption peak spanning 385–560 K, centered at around 495 K, which was attributed to the desorption of NH 3 adsorbed on weak acid centers according to the literature .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For Ag 2 O/SiO 2 –TiO 2 -50, the peak at 1445 cm –1 shifted to a higher wavenumber (1448 cm –1 ), which was attributed to Lewis acid center-bonded pyridine, and another peak at 1489 cm –1 appeared, which was assigned to either the Lewis acid center or the Brönsted acid center. However, no peak at around 1540 cm –1 was observed. , The case indicated that the incorporation of Ti into Ag 2 O/SiO 2 -50 led to the appearance of Lewis acid sites. As displayed in Figure b, the NH 3 -TPD profile of Ag 2 O/SiO 2 -50 showed no evident peak, indicative of the negligible acidity and the weak interaction of NH 3 with Ag + , which was desorbed by purging at a temperature of 393 K. Ag 2 O/SiO 2 –TiO 2 -50 showed a broad NH 3 desorption peak spanning 385–560 K, centered at around 495 K, which was attributed to the desorption of NH 3 adsorbed on weak acid centers according to the literature .…”
Section: Resultsmentioning
confidence: 93%
“…However, no peak at around 1540 cm −1 was observed. 39,40 The case indicated that the incorporation of Ti into Ag In other words, the incorporation of Ti into Ag 2 O/SiO 2 -50 led to an increase in the actual incorporation rate of Ag species and the appearance of weak Lewis acid sites on the surface; simultaneously, the mesoporous structure and the larger S BET were also sustained. interaction, where thiophene acted as a Lewis base.…”
Section: Introductionmentioning
confidence: 99%
“…It has large pore size (1.5-10 nm), high specific surface area (over 700m 2 /g) and high adsorption capacity, which has the properties required for the adsorption material [21]. Moreover, the removal of the template exposed some active sites, which provided binding sites for the sulfide and improved the removal efficiency of the sulfide [22]. Its pore size is similar to that of DBT, and it can be stabilized in water and in simulated oil (n-heptane-DBT).…”
Section: Figure 1 Catalytic Hydrodesulfurization Processmentioning
confidence: 99%
“…Desulfurization of liquid hydrocarbon fuels has attracted wide attention due to the severe atmospheric pollution caused by sulfur-containing fuel consumption. Governments have imposed more and more pressure on petroleum refineries to produce ultralow sulfur level fuel in view of environmental sustainability. Catalytic hydro-desulfurization technology is for now the most mainstream technique for the industrialization of removing mercaptans and thioether, but it is unreliable for eliminating aromatic sulfur compounds. Furthermore, catalytic hydro-desulfurization is conducted at high temperatures and pressures (>300 °C, hydrogen pressure of 20–100 atm), which require high energy consumption and come the side-effects of large octane loss. , One alternative technology, adsorptive desulfurization, has attracted enormous attention by virtue of its high efficiency, low consumption, and ultradeep desulfurization without changing the characteristics of gasoline . More importantly, liquid fuels with an ultralow sulfur content of less than 10 ppm can be achieved by adsorption desulfurization, which can meet the increasingly stringent vehicle exhaust regulations worldwide. …”
Section: Introductionmentioning
confidence: 99%
“…8−10 Furthermore, catalytic hydro-desulfurization is conducted at high temperatures and pressures (>300 °C, hydrogen pressure of 20−100 atm), which require high energy consumption and come the side-effects of large octane loss. 6,11 One alternative technology, adsorptive desulfurization, has attracted enormous attention by virtue of its high efficiency, low consumption, and ultradeep desulfurization without changing the characteristics of gasoline. 12 More importantly, liquid fuels with an ultralow sulfur content of less than 10 ppm can be achieved by adsorption desulfurization, which can meet the increasingly stringent vehicle exhaust regulations worldwide.…”
Section: ■ Introductionmentioning
confidence: 99%